A novel approach for securing images using visual cryptographic scheme - B R, Pushpa; Kumar B J, Santhosh (International Journal of Engineering and Technology, 2018)
Most applications require exchanging of information over insecure networks. The important issue concerned with respect to the images is to provide confidentiality and integrity. An efficient technique is proposed in order to provide protection to significant images through the digi-tal encryption scheme. Encryption before transmission is necessary for these images such that it makes sure that unauthorized person fails to access to any information. An efficient visual cryptographic approach is proposed for securing images by providing encryption during transferring an images or storing them. The technique proposed ensures that the images are inaccessible by unauthorized persons and also certifies confidentiality. In this proposed method to enhance security during data transmission across the network first the original image gets divided into multiple shares using logic operations and hence encryption technique is employed to these shares to maintain security. The binding of encryption and shares together called as encrypted shares are delivered and at the receiver side the reverse operation is carried out to retrieve back the original image. In the decryption process the decrypted share are layered to extract the actual image and if any shares are lost it is difficult to retrieve the information. The experimental result of the proposed method validates that the method will efficiently encrypt the image with a reduced amount of time without increasing the pixel size.Â Â